A Prática do Professor que Ensina Matemática e a Colaboração: uma reflexão a partir de processos formativos virtuais - Miskulin, Rosana Giaretta Sguerra [UNESP]; Penteado, Miriam Godoy [UNESP]; Richit, Andriceli [UNESP]; Mariano, Carla Regina [UNESP] (My University, 2011)
This text presents some reflections about the educational and virtual processes of mathematics teachers drawing on research on the theme. Thus, in this text, considering our experiences with the development of online courses, we discuss issues such as collaboration in virtual environments, which contributes to more effective results in collaborative learning and reduces the potential of isolation of student/teacher that can occur in virtual environments. Through collaborative learning in a virtual community, students/teachers have the opportunity to practice and think in-depth about their learning experiences by sharing new ideas with the group and receiving critical and constructive feedback. Moreover, the virtuality formed by the environment of online courses supports educational spaces for teachers who teach mathematics. Thus, collaboration emerges as an essential element for construction of meanings and for sharing experiences on the practice of teaching.
The practice of mathematics teachers and collaboration: A reflection from virtual educational processes
Keywords: Collaboration; Educational and virtual processes; Environment virtual